2007
DOI: 10.1111/j.1744-9987.2007.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status and the Use of Non‐Steroidal Anti‐Inflammatory Drugs in Hemodialysis Patients

Abstract: We examined whether the use of non-steroidal anti-inflammatory drugs (NSAIDs) can affect the anemia and iron status of hemodialysis patients. We recruited patients from six dialysis centers who had undergone maintenance hemodialysis for at least four months. We examined the use of NSAIDs during the past three months based on their medical records and assigned the patients to three groups (group A, non-NSAID group; group B, aspirin group; and group C, non-aspirin NSAID group). Of the 446 patients, 95 (21.3%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As mentioned above, small intestinal abnormalities in HD patients might be caused by multiple factors such as uremia, NSAID and/or low-dose aspirin use, and microcirculatory disorders. Other studies have found that uremia can cause gastrointestinal mucosal abnormalities 3 29 ; non-aspirin NSAID users had a higher incidence (71 %) of small intestinal mucosal injury 28 ; non-aspirin NSAID use decreased the serum iron level of HD patients 30 ; and low-dose aspirin can cause small intestinal mucosal injury 31 32 33 . The small bowel abnormalities might be a reflection of multiple complicating disorders, demonstrating their impact on prognosis.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned above, small intestinal abnormalities in HD patients might be caused by multiple factors such as uremia, NSAID and/or low-dose aspirin use, and microcirculatory disorders. Other studies have found that uremia can cause gastrointestinal mucosal abnormalities 3 29 ; non-aspirin NSAID users had a higher incidence (71 %) of small intestinal mucosal injury 28 ; non-aspirin NSAID use decreased the serum iron level of HD patients 30 ; and low-dose aspirin can cause small intestinal mucosal injury 31 32 33 . The small bowel abnormalities might be a reflection of multiple complicating disorders, demonstrating their impact on prognosis.…”
Section: Discussionmentioning
confidence: 96%
“…Another hypertensive drug, amlodipine, was reported to decrease iron overload and to reduce ferritin levels in patients with thalassemia major [ 47 ]. Nonsteroidal anti-inflammatory drugs (NSAIDs) (loxoprofen, diclofenac, ampiroxicam, naproxen, etodolac) are supposed to increase the risk of iron deficiency in chronic hemodialysis patients, according to Wang et al [ 52 ]. However, acetylsalicylic acid in a representative cohort did not affect serum iron or iron saturation [ 48 ].…”
Section: Pharmacotherapy and Iron Turnover In Transplant Patientsmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs, when taken regularly, may cause bleeding from the gastrointestinal tract and iron loss with the blood. The use of aspirin and other medicines belonging to this group of drugs may therefore increase the risk of iron deficiency, which can be identified as a low hemoglobin and serum ferritin concentration [4,7].…”
mentioning
confidence: 99%